Laparoscopic Nephroureterectomy with Concomitant Open Bladder Cuff Excision: A Single Center Experience - Ziaee, Seyed Amir Mohsen; Azizi, Valiollah; Nouralizadeh, Akbar; Gooran, Shahram; Radfar, Mohammad Hadi; Mirzaei, Mahboobeh (Urology Journal, 2012)
<span style="line-height: 107%; font-family: "Calibri","sans-serif"; letter-spacing: -0.1pt; color: #f36f21; font-size: 10pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">PURPOSE:<span style="line-height: 107%; font-family: "Calibri","sans-serif"; letter-spacing: -0.1pt; font-size: 10pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB"> To evaluate the efficacy of laparoscopic nephroureterectomy and open bladder cuff excision for management of upper urinary tract urothelial carcinoma. MATERIALS AND METHODS: Twenty-two patients with upper urinary tract urothelial carcinoma, who had undergone laparoscopic nephroureterectomy and open bladder cuff excision between September 2004 and October 2010, were studied retrospectively. Operation time, blood loss, analgesic dose, and complications were recorded. Local and port site recurrence, distant metastasis, and survival rate were also evaluated. RESULTS: Patients consisted of 18 men and 4 women, with the mean age of 64.1 years (range, 52 to 83 years). Right upper urinary tract was the involved site in 12 patients and left in 10 patients. Mean operation time was 216 minutes (range, 145 to 395 minutes) and mean hospital stay was 4.3 days. Mean follow-up period was 36.57 months (range, 6 to 65 months). No trocar site recurrence occurred. Three-year overall survival and metastasis-free survival were 95% and 90%, respectively. CONCLUSION: Laparoscopic nephroureterectomy along with open bladder cuff excision harbors an advantage of laparoscopy concomitant with simplicity and safety of open excision of distal ureter and bladder cuff through the same inevitable incision that is needed for specimen retrieval, without adding any more morbidity to the patient, a win-win radical surgery.